If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -1c = 10 Solving 14 + -1c = 10 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -1c = 10 + -14 Combine like terms: 14 + -14 = 0 0 + -1c = 10 + -14 -1c = 10 + -14 Combine like terms: 10 + -14 = -4 -1c = -4 Divide each side by '-1'. c = 4 Simplifying c = 4
| 2x+7=9x+7 | | 2x(x-2)=x^2 | | r-8/2=4 | | 16x+3=21x-7 | | 2x^2+7x-15=f(x) | | 7-3(6n-2)=-2n-35 | | 11d+8=7d+24 | | -12/p=3 | | ((120*2x)/2)=4x | | 5(2x-4)-9x=6 | | 3s-4=14 | | 2y^2-y+53=(y+5)(y+5) | | 7x-4y+12=0 | | 2(d-5)=18 | | 7(4y-9)= | | g^6+12g^3+36=0 | | 4a+27=9n-8 | | 2v^2+9v-10=(v+2)(v+2) | | 7c^2-21c+14=0 | | 4z-16=2+2 | | 2(w-20)=-16 | | 2x^2+23x+67=(x+7)(x+7) | | p^2-16pq+63q^2=0 | | 2x^2+23x+67=0 | | 3d+9e+7d+7e= | | 3x-2=7x-6 | | 3(2n-1)+7n= | | 7+2b=2(4b+7)+5 | | 3.(x+2)=15-2x | | 2a^2+15=11a | | -5k+24=49 | | 3(x+2)=15-2x |